Antidumping: Un problema para la industria del calzado - Cavero Guevara, Miriam Roxana (2024)
The objective of this study was to analyze whether antidumping corrects the dumping of footwear from China and whether it is a problem for imports. Whose method employed was explanatory, quantitative and causal with non-experimental, longitudinal design, the population comprises 1,866,488 and the sample of 763507, series of customs declarations of footwear imported into Peru. time series 2010-2019, obtained from SUNAT. The VAR models were used through the MGM and MCVE, Levene's test and t-test for difference of means indicates that it is significant <0.05. It was determined that antidumping is not the policy that corrects the dumping problem and did not affect the imports.